Varieties of Social Investment Policies on Two Sides of the Baltic Sea: Explaining Routes to Endurance. (4th June 2017) - Toots, Anu; Lauri, Triin
Abstract: By 2016, European countries have more or less recovered from the 2008 recession. However, the strategies for coping with the crisis have varied, and one of the main concerns is to which extent the social investment paradigm has survived. In this article, we first map the dynamics of social investment expenditures in 2004–12 in six low‐ and high‐spending welfare states in the Baltic Sea region – Estonia, Latvia, Lithuania, Finland, Denmark and Sweden – and define countries which have managed to sustain the social investment ratio after recession. Second, by employing fuzzy‐set Qualitative Comparative Analysis, we explore the configurational routes of ideational and structural factors within various macroeconomic contexts associated with the endurance of social investment. The analysis revealed that two out of the six countries – Denmark and Lithuania – managed to increase or preserve the share of investment expenditures in their total welfare budgets. Stable economic growth and low government debt turned out to be necessary conditions regardless of the generosity of the welfare state. However, while in Baltic countries a strong economy has to be in conjunction with ideational contributors (such as a government coalition of liberals and social democrats, and strict employment protection), the Nordic route includes a strong economy in conjunction with a high share of service economy.